Pola Komunikasi Interpersonal antara pelatih dan Atlet Catur Putri dalam membangun mental bertanding : studi kasus pada Atlet Catur Senior Putri Percasi Palembang - Fiansi Dwi Arista Cantika; Cindy Afriliani; Winda Agustina Saputri; Abdur Razzaq (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The purpose of this study is to examine how coaches and senior female chess players at Percasi Palembang communicate in building their competitive mentality. Communication between coaches and athletes is very important in the coaching process because this sport requires psychological endurance and strategic thinking skills. Through observation and interviews with coaches and female athletes, this study uses a qualitative approach with a case study method. The results of the study show that two main communication patterns are used in coaching: directive and collaborative patterns. The directive pattern is used to provide technical instructions, analyze positions, assess strategies, and provide immediate corrections to athletes' mistakes during training. Meanwhile, the collaborative pattern emerges through two-way discussions, openness, empathy, emotional support, and the development of psychological closeness; these two patterns make athletes feel more comfortable in expressing their mental and strategic obstacles. This boosts athletes' confidence, mental resilience, and competitive focus. With good communication, training becomes more enjoyable, athletes are more involved in strategy analysis, and they are better prepared for the pressure of competition. The results of this study show that the quality of the emotional and intellectual relationship between coaches and athletes is an important foundation for building mental preparedness for competition. Therefore, to support the competitive performance of chess players, coaches must improve their interpersonal communication skills.